Apriori Algorithm in Electrical Equipment Sales for Inventory Control Optimization - Jupron; Okta Irawati; Muhammad Bahrein (Jurnal Inotera, 2025)
XYZ Electrical Store is one of the small and medium enterprises that sells various types of electrical equipment for household needs. The management of sales data in the store is still done by recording sales transactions in a book, making the sales report generation process take a long time. With such a sales data management system, control and planning of stock items become less than optimal. Customers often find that the items they want to buy are out of stock. Moreover, the accumulation of less popular items also poses a challenge to the store's cash flow, resulting in subopti mal business processes. This research was conducted to address the issues of controlling and planning stock of goods using data mining techniques with the Apriori algorithm on sales transactions of electrical tools. Through a series of threshold tests, a minsup of 10% and minconf of 60% were obtained. This study results in information on the types of electrical tools that need to be monitored as they can lead to stock shortages when buyers need them, namely, the categories of LED lights, electrical cables, plugs, electrical insulation, and out bow. By knowing this information, it can provide solutions to Sinar Mulya Electric Store in stocking the most frequen tly sold items in the store.